2009
DOI: 10.1037/a0014067
|View full text |Cite
|
Sign up to set email alerts
|

Influence of caring youth sport contexts on efficacy-related beliefs and social behaviors.

Abstract: Understanding what factors influence positive youth development has been advocated by youth development researchers (P. L. Benson, 2006; J. S. Eccles & J. A. Gootman, 2002). Consequently, the purpose of this study was to examine whether perceptions of a caring youth sport context influenced prosocial and antisocial behavior through efficacy-related beliefs, that is, positive and negative affective self-regulatory efficacy (ASRE) and empathic self-efficacy (ESE). Multiethnic youths taking part in summer sport p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
111
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 63 publications
11
111
1
7
Order By: Relevance
“…Fostering a respectful, fair, safe, welcoming, and comfortable environment may enhance leaders' opportunities to understand and accept participants for who they are . Gano-Overway et al (2009) found that individuals' perceptions of a caring climate had a positive effect on their pro-social behavior and empathetic abilities, which decreased their antisocial behavior, as well. Additionally, when exercise participants perceived the climate to be both highly caring and task-involving, they reported significantly increased effort, enjoyment, and expected future participation Gano-Overway et al, 2009).…”
Section: Psychometric Support For the Ownership In Exercise And Empowmentioning
confidence: 99%
See 3 more Smart Citations
“…Fostering a respectful, fair, safe, welcoming, and comfortable environment may enhance leaders' opportunities to understand and accept participants for who they are . Gano-Overway et al (2009) found that individuals' perceptions of a caring climate had a positive effect on their pro-social behavior and empathetic abilities, which decreased their antisocial behavior, as well. Additionally, when exercise participants perceived the climate to be both highly caring and task-involving, they reported significantly increased effort, enjoyment, and expected future participation Gano-Overway et al, 2009).…”
Section: Psychometric Support For the Ownership In Exercise And Empowmentioning
confidence: 99%
“…In a task-involving climate participants' effort and improvement are recognized, every individual plays an important role, and cooperation is fostered (Newton et al, 2000). When participants perceive a task-involving climate to be emphasized, they have consistently reported more positive outcomes, such as significantly more enjoyment, effort, positive relationships with teammates/coaches, and increased interest in future participation (Duda & Nicholls, 1992;Gano-Overway et al, 2005;Gano-Overway et al, 2009;Seifriz, Duda, & Chi, 1992;Walling, Duda, & Chi, 1993). In contrast, in an ego-involving climate individuals' ability and improvement are judged against normative standards and peer comparison, leaders employ greater use of punishment for mistakes or poor performance, and leaders consistently give more attention and praise to the few with the highest ability (Newton et al, 2000).…”
Section: Psychometric Support For the Ownership In Exercise And Empowmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants responded to the items with a 5-point scale ranging from 1 (strongly disagree) to 5 (strongly agree). The CCS has consistently demonstrated strong measurement reliability, .92 to .96, and been associated with concurrent validity constructs in theory-hypothesized directions and magnitudes (Gano-Overway et al, 2009;Newton et al, 2007). For example, Newton et al (2007) found the caring climate to have a moderate, positive correlation with the task-involving climate (r = .56) and a moderately small, negative correlation with the ego-involving climate (r = -.36).…”
Section: Caring Climate Scale (Ccs)mentioning
confidence: 99%